The Impact of Product and Process Strategies on the Service Performance: The Mediating Role of Supply Chain Integrations - Benjabhon Mee-ngoen; Chairit Thongrawd; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The main purpose of the current study is to investigate he relationship between product and process strategies and the service performance namely delivery performance and the support performance. In addition to that the study has also examined the mediating role of supply chain integrations namely supplier integration and customer integration in the relationship between product and process strategies and the service performance. In this research, Product Modularity is the specific product and Process Modularity is the process strategy, which has been selected. The performance of service is influenced by these two strategies in a direct and indirect way. The focus of the study is on the evaluation of the level to which the supplier (upstream) as well as customer (downstream) integration mediates the impact of process strategies on performance of services. The study is among the pioneering studies on the issues. So, current study has used SEM-PLS as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the current study have provided support to with the hypothesized results. This study will be helpful for policymakers and researchers in examining the link between product and process strategies and the service performance namely delivery performance and the support performance.